RASIONALISME SEBAGAI CABANG FILSAFAT DAN PENGARUHNYA PADA TAFSIR AL-MANAR - Darmawan, Kasis (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This study discusses the influence of rationalism as a branch of philosophy on the methods and approaches to al-Manar's interpretation. Rationalism, which places reason as the main tool in understanding reality, is an important element in building a rational and contextual approach to interpretation. In their interpretation of al-Manar, Muhammad Abduh and Rasyid Ridha try to harmonize revelation and reason to answer the challenges of modernism, such as social reform, education and the revival of Muslims. This research shows that the influence of rationalism is reflected in the efforts of al-Manar's interpretation to provide explanations that are logical, applicable and relevant to the socio-political conditions of his time. This approach not only emphasizes textual aspects, but also considers moral and social aspects, making this tafsir one of the progressive works in Islamic studies. In conclusion, rationalism enriches interpretive methodology by opening space for dialogue between revelation and contemporary reality, resulting in a more relevant and inclusive understanding. These findings emphasize the role of philosophy, especially rationalism, in supporting the development of Islamic studies that are adaptive to changing times